1987
DOI: 10.2134/agronj1987.00021962007900060023x
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphology and Vigor Effects on Winter Heaving of Established Alfalfa1

Abstract: There has been considerable speculation regarding the influence of root system morphology on the susceptibility of alfalfa (Medicago sativa L.) to frost heaving injury. This field study represents a first attempt at quantification of that relationship. A tagging technique was developed for monitoring heave of established alfalfa plants during winter. Measurements were made on a Collamer silt loam (Glossoboric Hapludalf) intergrading to a Niagara silt loam (Aeric Ochraqualf) near Ithaca, NY. Final (net) crown d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Shimada et al (1982) showed that heaving resistance is weak in alfalfa plants having a straight deep tap root with few branch roots. Perfect et al (1987) found that alfalfa plants with a broken taproot experienced greater soil heaving in midwinter. Gill (1977) studied the susceptibility of 16 onion varieties to frost heaving and found that root number and length played an important role.…”
Section: Root Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Shimada et al (1982) showed that heaving resistance is weak in alfalfa plants having a straight deep tap root with few branch roots. Perfect et al (1987) found that alfalfa plants with a broken taproot experienced greater soil heaving in midwinter. Gill (1977) studied the susceptibility of 16 onion varieties to frost heaving and found that root number and length played an important role.…”
Section: Root Systemmentioning
confidence: 99%
“…x Biswell et al 1953MacGillivray and Hartley 1973Soderstriim 1973 x Low 1969, 1975Shaw et al 1987Zalasky 1980I Graber 197 1 Sutton 1968, 1991, 1992Haasis 1923Shimada et al 1982cox 1979Gill 1977Kinbacher 1956Cox and Mason 1955Biswell et al 1953Lamb 1936 Factors Factors affecting forest heaving of forest tree species and agricultural crops Haasis 1923Brink et al 1967Russell et al 1978Sutton 1969, 1992Cooper 1940Perfect et al 1987Shimada et al 1982;Portz 1967Gill 1977 Hook. and Am.)…”
Section: Loss Of Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific root traits have been correlated with better persistence in these crops. In alfalfa, root branching (Perfect et al, 1987) or creeping roots (Heinrichs & Morley, 1960) and number of secondary roots (Hansen & Viands, 1989) have been positively associated with better persistence. Adventitious roots originating from the crown are thought to promote better persistence in red clover.…”
Section: Introductionmentioning
confidence: 99%